Antimicrobial activity of chitosan isolated from fungus Rhizopusoryzae - Kawthar Tuma Khalaf (Al-Qadisiyah Journal of Pure Science, 2018)
In this study chitosan was isolated from the fungus Rhizopusorayzae by using yeast peptone glucose broth medium (YPG) at the late stationary phase. Chitosan production from mycelium reached to 15 mg/g as dry weight . 25% was the Nacetylation of chitosan while 96% for the D-glucosamine. Chitosan showed antimicrobial activity against Escherichia coli, Staphylococcus aureus and Candida albicans and reach to 20 , 15 and n 15 mm as inhibition zone respectively .